Comparative in vitro investigation of the cariogenic potential of bifidobacteria. (November 2016) - Valdez, Remberto Marcelo Argandoña; dos Santos, Vanessa Rodrigues; Caiaffa, Karina Sampaio; Danelon, Marcelle; Arthur, Rodrigo Alex; Negrini, Thais de Cássia; Delbem, Alberto Carlos Botazzo; Duque, Cristiane
Highlights: Bifidobacterium animalis and Bifidobacterium longum have acidogenic and aciduric potential similar to cariogenic bacteria. Higher biofilm formation is observed when B. longum and B. animalis are combined with S. mutans and S. sobrinus . B. longum and B. animalis when associated with S. mutans and S. sobrinus caused higher enamel demineralization. Some species of Bifidobacterium could contribute to the progression of carious lesions. Abstract: Objective: This study aimed to assess the in vitro cariogenic potential of some Bifidobacterium species in comparison with caries-associated bacteria. Design: Bifidobacterium lactis, Bifidobacterium longum, Bifidobacterium animalis, Bifidobacterium dentium, Lactobacillus acidophilus, Lactobacillus casei, Actinomyces israelii, Streptococcus sobrinus and Streptococcus mutans were tested for acidogenicity and aciduricity by measuring the pH of the cultures after growth in glucose and bacterial growth after exposure to acid solutions. Biofilm biomass was determined for each species either alone or associated with S. mutans or S. mutans / S. sobrinus . Enamel hardness was analyzed before and after 7-days biofilm formation using bacterial combinations. Results: B. animalis and B. longum were the most acidogenic and aciduric strains, comparable to caries-associated bacteria, such as S. mutans and L. casei . All species had a significantly increased biofilm when combined either with S. mutans or with S . mutans / S. sobrinus . The greatest enamel surface loss was produced when B. longum or B. animalis were inoculated with S. mutans, similar to L. casei and S. sobrinus . All strains induced similar enamel demineralization when combined with S . mutans / S. sobrinus, except by B. lactis . Conclusion: The ability to produce acidic environments and to enhance biofilm formation leading to increased demineralization may mean that Bifidobacterium species, especially B. animalis and B. longum, are potentially cariogenic.